The Effect of Disclosure of Sustainable Development Goals on the Financial Performance of Banking Companies in Indonesia - Mahardyastika Laksmita Arnanda (Journal of Social Research, 2024)
This study aims to analyze the impact of Sustainable Development Goals (SDG) disclosure on the Return On Assets (ROA) of banking companies in Indonesia, to analyze the impact of SDG disclosure on the Return On Equity (ROE) of banking companies in Indonesia, and to analyze the impact of SDG disclosure on the Return On Investment (ROI) of banking companies in Indonesia. The data used in this research are secondary data sourced from the Annual Reports and Sustainability Reports of financial service companies in the banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The research sample was selected using purposive sampling method, resulting in 15 companies as samples. The data analysis used for hypothesis testing is panel data analysis using Eviews 12 software. The results of the study indicate that SDG disclosure has a positive effect on ROA, SDG disclosure has a positive effect on ROE, and SDG disclosure has a positive effect on ROI of banking companies in Indonesia. These findings provide important empirical evidence that can encourage banking companies to pay more attention to and integrate SDGs into sustainable business strategies to achieve optimal financial performance, and promote more comprehensive and transparent SDG disclosure regulations to help investors make better investment decisions, as well as encourage investors to consider sustainability factors in their investment decisions. The implication of this research is the encouragement for banking companies to pay more attention and integrate SDGs in business strategy.